Nephrolithiasis Associated with Nephrocalcinosis Is Primarily Composed of Carbonate Apatite - Teresa Antonia Kiener; Elena Moré; Michael Franzen; Janne Cadamuro; Christoph Schwarz; Carsten Bergmann; Hermann Salmhofer (Kidney & Blood Pressure Research, 2024)
Introduction: This study was designed to determine the mineral composition of calculi in nephrocalcinosis with nephrolithiasis, diagnose the underlying disease, and monitor the course of renal function in patients with nephrocalcinosis-nephrolithiasis. Methods: Renal calculi extruded in a series of 8 patients with nephrocalcinosis were analysed using Fourier transmission infrared spectrometry. In 4 patients, next-generation sequencing using a nephrocalcinosis-nephrolithiasis panel was performed to determine the nature of the underlying disease. In addition, longitudinal analysis of renal function was performed in all patients. Results: Seven patients revealed carbonate apatite as the sole constituent of renal calculi. One patient showed a mixed composition of dicalcium phosphate dihydrate/carbonate apatite at first analysis yet in subsequent episodes also had calculi composed of pure carbonate apatite. Further molecular analysis displayed distal renal tubular acidosis in 2 of 4 patients who consented to sequencing. No known genetic defect could be found in the other two cases. In line with prior reports, decline of renal function was dependent on underlying disease. Distal renal tubular acidosis revealed a progressive course of renal failure, whereas other causes showed stable renal function in long term analysis. Conclusion: Nephrocalcinosis with nephrolithiasis is a rare condition with heterogeneous aetiology. Yet mineral composition of renal calculi predominantly consisted of pure carbonate apatite. This uniform finding is similar to subcutaneous calcifications of various origins and might propose a general principle of tissue calcification. Progressive decline of renal function was found in distal renal tubular acidosis, whereas other conditions remained stable over time.